Mitigating the Impact of Admixtures in Thai Herbal Products - Urumarudappa, Santhosh Kumar J.; Tungphatthong, Chayapol; Sukrong, Suchada (Frontiers in Pharmacology, 2019)
Abstract: Medicinal plants and their products are extensively used within indigenous healthcare systems in Thailand and several other nations. The international trade of herbal products has a noteworthy impact on the worldwide economy, and the interest in herbal products is expanding in both developing and developed countries. There has been rapid growth in the medicinal plant product market and a broadening consumer base interested in herbal products from Thailand. However, in herbal industries, ingredient substitution and admixture are typical issues wherein species of lower market value are admixed with those of a higher value. The adverse consequences of consuming adulterated drugs are invariably due to the presence of an unintended herb rather than the presence of an intended herb. It has also been argued that admixtures are intentional because of the lack of regulatory policies or centralized tests for product authentication. The consequences of species admixtures can extend from the reduced efficacy of a drug to decreased trade value. This study aims to clarify the nature and extent of species admixtures reported in the Thai herbal trade market and discuss the potential reasons for such adulteration. In the broader context of species admixtures, we strongly propose the establishment of multiple herbal crude drug repositories that can be developed to facilitate the use of comparative identity tests by industry, traders and researchers to maintain authentic natural health product (NHP) standards and to certify the authenticity of NHPs. The proposition of the establishment of centralized testing (CT) could be a promising initiative in Thailand for the development of science and technology, and the herbal medicines produced as a result of centralized testing could be dispensed as prescription drugs based on disease consideration instead of as health foods or nutraceuticals.